Antibacterial efficacy of three root canal sealers against Enterococcus faecalis and Candida albicans: An in vitro study - Rahul Bhargava; K Shashikala; Rangoli Bhargava (Wolters Kluwer Medknow Publications, 2015)
Aim: The aim of this in vitro study was to compare the antimicrobial efficacy of calcium hydroxide-based sealer (Apexit Plus), zinc oxide eugenol-based sealer (Endoflas FS) and resin-based sealer (EndoRez) root canal sealers against Enterococcus faecalis microbial type culture collection (MTCC) 439 and Candida albicans MTCC 239 using agar diffusion test. Materials and Methods: In the present study, 20 Mueller Hinton agar (MH agar) plates were employed. Three wells were made by removal of agar at equidistant points and filled with root canal sealers according to manufacturer's instructions. The strains of the bacteria and fungi used in this study were E. faecalis MTCC 439 and C. albicans MTCC 227. Both micro organisms were grown at 37°C for 24 h in MH Broth and seeded into MH agar to produce a turbidity of 0.5 on the McFarland scale, which corresponds to a concentration of 10 8 CFU/mL. This MH broth was used as a second layer. The seeded agar was then added over the plates immediately after the insertion of sealer cements. After incubation, the diameters of zones of inhibition around the plates were measured. Results: The results were statistically analyzed using two way ANOVA test. Against both the micro organisms used in this study, Endoflas FS showed the largest zones of inhibition followed by Apexit Plus and EndoRez. Conclusion: Within the limitations of this study, it can be concluded that: Root canal sealers showed different inhibitory effects depending on their types and microbial strains tested. Against Enterococcus faecalis and Candida albicans, zinc oxide based sealers showed the highest microbial zones of inhibition followed by the calcium hydroxide based sealer and resin based sealer respectively